2012
DOI: 10.1021/cm2031009
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-Deficient TiO2−δ Nanoparticles via Hydrogen Reduction for High Rate Capability Lithium Batteries

Abstract: The interest of exploring environmentally benign and safe anode materials for lithium batteries has led to TiO 2 (anatase) nanostructures as promising candidates. However, the poor chemical diffusion of lithium in the materials still limits the rate capability. We report on the high rate capability of lithium storage with oxygen-deficient TiO 2−δ nanoparticles prepared by hydrogen reduction. A systematic study on the effect of electronic charge carrier concentration on the overall electrochemical lithium stora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
423
3
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 384 publications
(452 citation statements)
references
References 49 publications
22
423
3
2
Order By: Relevance
“…Long-range order of vacancies leads to crystallographic shear and transformation into the Magnéli phases (Ti n O 2n-1 , n>3 [20]). These substoichiometric phases have been widely observed in TiO 2 thin films [11], nanoparticles [21] and nanowires [22]. Due to the metallic conductivity, they have been widely considered as possible electrode materials in batteries and fuel cells [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Long-range order of vacancies leads to crystallographic shear and transformation into the Magnéli phases (Ti n O 2n-1 , n>3 [20]). These substoichiometric phases have been widely observed in TiO 2 thin films [11], nanoparticles [21] and nanowires [22]. Due to the metallic conductivity, they have been widely considered as possible electrode materials in batteries and fuel cells [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [28] revealed the dynamic lithiation process at the surface of single crystal silicon with atomic resolution. Recently, it has been shown that the cation and oxygen deficiency in transitional metal oxides, such as manganese oxides, titanium oxides, vanadium oxides, iron oxides and tin oxides, can be confirmed by using HRTEM [29][30][31][32][33][34]. However, it should be noted that one may run the risk of error in correlating HRTEM image to the atomic structures of specimens, since the contrast in HRTEM images changes dramatically with specimen thickness and defocus, owing to the so-called multiple scattering effect, and is also strongly dependent on the resolution of the microscopy [35,36].…”
Section: Hrtemmentioning
confidence: 99%
“…[25,49,61] Meanwhile, there are a few reports mentioning possible decrease in the photocatalytic activities, if the hydrogenated TiO 2 nanomaterials are not properly prepared. [37,38] So far, hydrogenation has been conducted on TiO 2 nanoparticles, [4,21,31] nanorods, [48] nanotubes, [45] nanowires, [46] nanosheets, [35,36] with anatase or rutile phase, [4,29,33] under high-pressure, [4,21] ambient pressure, [29,30,39] or low-pressure [43] pure hydrogen environment, or hydrogen-argon, [44][45][46][47][48] hydrogen-nitrogen [52][53][54] gas flow, in the temperature range from room temperature [21] to 700°C, [27] with a hydrogenation time from a few minutes [27] to 20 days. [21] With no doubt, we can image that the so-formed TiO 2 nanomaterials will display variations in their characteristics and performances.…”
Section: +mentioning
confidence: 99%
“…[48] The improved electrical conductivity of the hydrogenated TiO 2 nanorods benefits the photoelectrochemical sensing of various organic compounds: glucose, malonic acid and potassium hydrogen phthalate under visible light. [41] Improved performances are observed when using hydrogenated TiO 2 nanomaterials as the active anode materials in lithium-ion rechargeable batteries, due to the creation of oxygen vacancies, [28,44] the existence of Ti 3+ ions, [46] the well-balanced Li + /e − diffusion, [44] the increased electronic conductivity, [28,39,44,46] reduced charge diffusion resistance, [76] or the pseudocapacitive lithium storage on the disordered particle surface. [55] For example, the short lithium-ion diffusion path and the high electronic conductivity in the hydrogenated mesoporous TiO 2 microspheres improved the lithium-ion capacity and rate capability of mesoporous TiO 2 microspheres (Fig.…”
Section: +mentioning
confidence: 99%